Estimativas do Consumo e da Taxa de Passagem do Capim-Elefante (Pennisetum purpureum Schum.) sob Pastejo de Vacas em Lactação - Soares, João Paulo Guimarães; Aroeira, Luiz Januário Magalhães [UNESP]; Verneque, Rui da Silva; Pereira, Odilon Gomes; Martins, Carlos Eugênio; Valadares Filho, Sebastião de Campos; Ferreira, William José (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2001)
The voluntary dry matter intake (DMI), rate of passage and mean retention time in the rumen and gastrointestinal tract were estimated using IS crossbred Holstein-Zebu lactating cows grazing elephantgrass. The voluntary DMI and fecal output estimations the models proposed by QUIROZ et al. (1988) and POND et al. (1989) were used. The data of rate of passage and those of retention time in the rumen the model suggested by GROVUM and WILLIAMS (1973) was chosen. The elephantgrass pasture were fertilized and managed in a rotational system with three days paddock occupation and 30 days resting. The stocking rate was 6 cows/ha. The DMI was estimated using the relation fecal output/forage indigestibility of extrusa samples. For the fecal production calculations, neutral detergent fiber was chromium mordanted. Using the models of POND et al. (1989) and QUIROZ et al. (1988) to compare the total diet DMI (12.5 and 13.9 kg/cow/day) and elephantgrass DMI (7.7 and 9.2 kg/cow/day) they did not differ, respectively. However, the rate of passage and the mean retention time in the gastrointestinal tract did differ among the three used models. The results of this trial showed that the model proposed by QUIROZ et al. (1988) was the one that better describes the DMI data.
Estimates of feed intake and rate of passage of elephantgrass (Pennisetum purpureum Schum.) under grazing conditions using lactating cows
Keywords: chromium mordent; elephantgrass; intake; lactating cows; models; passage rate